Investigation of PM2.5-induced carcinogenic effects through mediation of ErbB family based on DNA methylation and transcriptomics analysis by a lung-mimicking microfluidic platform - Lulu Zheng; Yuwen Wang; Yule Zhang; Zongtao Chai; Sixiu Liu; Bo Wang; Bo Dai; Dawei Zhang (Ecotoxicology and Environmental Safety, 2022)
Fine particle (PM2.5, less than 2.5 micrometers in diameter) is regarded as a harmful carcinogen. However, the molecular mechanisms of the carcinogenic effects of ambient fine particles have not been fully elucidated, and therapeutic options to address this major public health challenge are lacking. Here, we present global gene-specific DNA methylation and transcriptomic (RNA-Seq) analyses after HBE cells were exposed to fine particles on a portable, small, and all-in-one organ-level lung-mimicking air-liquid interface exposure (MALIE) microfluidic platform. A series of cancer-related signal transduction pathways were activated. ErbB1, ErbB2, and ErbB3 gene expression altered by fine particle exposure was the result of changes in the cellular DNA methylome. The protein expression of ErbB family was inhibited by drugs and could regulate downstream Grb2/Raf pathway and Akt/MDM2 pathway. All of the above results indicated that ErbB family may be promising drug targets for air pollution-related diseases and that inhibitor drugs can be used as therapeutic options to treat these diseases.